2019
DOI: 10.1080/10942912.2019.1580719
|View full text |Cite
|
Sign up to set email alerts
|

Freshness assessment of shrimp Metapenaeus affinis by quality index method and estimation of its shelf life

Abstract: This study aimed to develop a Quality Index Method (QIM) for ice stored Metapenaeus affinis, and estimate its shelf life of shrimp during 12 days of storage analyzing periodically microbiological (total mesophilic (TMC), psychrotrophilic (PTC), physicochemical (TVB-N, TMA, pH, TBARS and FFA), and sensory (Quality Index Method protocol) characteristics. Partial least squares (PLS) regression was used to correlate the QIM attributes, and linear regression analysis was used to check the variables as a function of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Thus, QIM could underestimate the shelf life of spiny lobster since the TVB-N value was below the acceptable limit on the 10th day. On the other hand, another recent study on monitoring crustacean shelf life showed that TVB-N levels increased up to 25 mg N/100 g after 10 days of storage, as described by Khodanazary (2019). TVB-N presented levels above 34 mg N/100 g in the ninth day of storage for shrimp (Metapenaeus affinis), as this index well correlated with the QIM results, since the sensory panel rejected the samples at the same day (Khodanazary, 2019).…”
Section: Tvb-nmentioning
confidence: 62%
See 4 more Smart Citations
“…Thus, QIM could underestimate the shelf life of spiny lobster since the TVB-N value was below the acceptable limit on the 10th day. On the other hand, another recent study on monitoring crustacean shelf life showed that TVB-N levels increased up to 25 mg N/100 g after 10 days of storage, as described by Khodanazary (2019). TVB-N presented levels above 34 mg N/100 g in the ninth day of storage for shrimp (Metapenaeus affinis), as this index well correlated with the QIM results, since the sensory panel rejected the samples at the same day (Khodanazary, 2019).…”
Section: Tvb-nmentioning
confidence: 62%
“…On the other hand, another recent study on monitoring crustacean shelf life showed that TVB-N levels increased up to 25 mg N/100 g after 10 days of storage, as described by Khodanazary (2019). TVB-N presented levels above 34 mg N/100 g in the ninth day of storage for shrimp (Metapenaeus affinis), as this index well correlated with the QIM results, since the sensory panel rejected the samples at the same day (Khodanazary, 2019). Moreover, the correlation of QIM with the TVB-N values becomes problematic when considering freshwater species, due to the absence of TMAO in vivo.…”
Section: Tvb-nmentioning
confidence: 88%
See 3 more Smart Citations